Chip-on-board assembly of 800V Si L-IGBTs for high performance ultra-compact LED drivers - Aliyu, Attahir Murtala; Mouawad, Bassem; Castellazzi, Alberto; Rajaguru, P.; Bailey, C.; Pathirana, V.; Udugampola, N.; Trajkovic, T.; Udrea, F. (2017)
This paper presents a novel chip on board assembly design for an integrated power switch, based on high power density 800V silicon lateral insulated-gate bipolar transistor (Si LIGBT) technology. LIGBTs offer much higher current densities (5-10X), significantly lower leakage currents, and lower parasitic device capacitances and, gate charge compared to conventional vertical MOSFETs commonly used in LED drivers. The higher voltage ratings offered (up to 1kV), the development of high voltage interconnection between parallel IGBTs, self-isolated nature and absence of termination region unlike in a vertical MOSFET makes these devices ideal for ultra-compact, low bill of materials (BOM) count LED drives. Chip on-board LIGBTs also offer significant advantages over MOSFETs due to high ambient temperatures seen on most of the LED lamps as the LIGBTs on-state losses increase only marginally with temperature. The design is based on a built-in reliability approach which focuses on a compact LED driver as a case-study of a cost-sensitive large volume production item.